Making human rights intelligible towards a sociology of human rights - Verschraegen, Gert 1973-; Madsen, Mikael Rask (Hart Publishing, 2013)
Making human rights intelligible : an introduction to a sociology of human rights /Mikael Rask Madsen and Gert Verschraegen --State building, constitutional rights and the social construction of norms : outline for a sociology of constitutions /Chris Thornhill --Differentiation and inclusion : a neglected sociological approach to fundamental rights /Gert Verschraegen --Beyond prescription : toward a reflexive sociology of human rights /Mikael Rask Madsen --Human rights between brute fact and articulated aspiration /Paul Stenner --International human rights versus democracy promotion : on two different meanings of human rights in US foreign policy /Nicolas Guilhot --Towards a socio-legal analysis of the European Convention on Human Rights /Steven Greer --In defence of societies /Judith Blau and Alberto Moncada --From citizenship to human rights to human rights education /Francisco O. Ramirez and Rennie Moon --(Human) rights and solidarity : restructuring the national welfare space /Frederik Thuesen --Adapting locally to international health and human rights standards : an alternative theoretical framework for progressive realisation /Lesley A. Jacobs --"Legal form" and the purchase of human rights discourse in domestic policy-making : the achievement of same-sex marriage in Canada /Luke McNamara --Activating the law : exploring the legal responses of NGOs to gross rights violations /Loveday Hodson --The complexities of human rights implementation within the Costa Rican police system /Quirine Eijkman.
Keywords: Human rights; Sociological jurisprudence